Barkhausen Noise Emission of Surfaces after Plasma Beam Machining - Micietova, Anna; Neslusan, Miroslav; Cillikova, Maria; Kolarik, Kamil (Manufacturing Technology Journal, 2016)
This paper deals with analysis of surface integrity of steel after plasma beam machining (PBM). The paper discusses surface integrity expressed in term of rms values of Barkhausen noise and reports about variables affecting Barkhausen noise emission such as plasma current, nozzle distance, thickness of machined surface and feed speed. The paper demonstrates variable degree of surface hardening due to elevated temperatures and the following rapid cooling. Except magnetic investigation of surface also stress state and structure observation are reported.
Keywords: Plasma Beam Machining; Barkhausen Noise; Surface Hardening